Grammatical Cohesion: An Analysis of Reference in ‘The Tell Tale Heart’of Edgar Allan Poe - Anna Maria Bertiana; I Gusti Ayu Vina Widiadnya Putri (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2026)
This study investigates how grammatical cohesion, particularly reference, is used to build meaning and narrative depth in Edgar Allan Poe’s short story The Tell-Tale Heart. The aim is to examine what types of reference are used and how they contribute to the story’s overall cohesion and psychological atmosphere. Using a qualitative descriptive approach, the analysis applies Halliday and Hasan’s model of reference, which includes personal, demonstrative, and comparative forms. The findings show that personal references, such as “I,” “my,” and “he”, are used extensively, shaping the story’s intense first-person perspective and reflecting the narrator’s obsessive mindset. Demonstrative references like “that eye” or “this work” highlight specific objects of fixation and carry symbolic meaning. Although less common, comparative references help express the narrator’s inflated sense of control and precision. Overall, the study finds that reference in Poe’s story does more than link sentences, it acts as a powerful stylistic tool that reveals character psychology and intensifies the narrative’s suspense. Keywords: grammatical cohesion, reference, stylistics, narrative, Edgar Allan Poe